ANALISIS RASIO LIKUIDITAS DAN RENTABILITAS SEBAGAI ALAT PENILAIAN KINERJA KEUANGAN PADA KOPERASI SIMPAN PINJAM PENGEMBANGAN PEDESAAN (KSP3) CABANG ALASA KABUPATEN NIAS UTARA - Fau, Erasma; Manao, Kei. S; Maduwu, Samuel; Finowaa, Kurbanus; Waoma, Rahel (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
This study examines liquidity and profitability ratio analysis as a tool for evaluating financial performance at the Rural Development Savings and Loans Cooperative (KSP3) Alasa Branch in North Nias Regency. The aim is to evaluate the cooperative’s financial performance through its financial statements. The data analysis method used is ratio analysis. From the liquidity ratio analysis, the current ratio from 2020 to 2023 ranges from 140.59% to 131.12%, indicating a fairly good financial condition. The quick ratio for the same period shows values between 135.76% and 120.69%, indicating very good financial conditions. However, the cash ratio, which ranges from 12.31% to 7.64%, indicates poor financial performance. On the other hand, the Cash Turnover Ratio between 2020 and 2023 ranges from 161.36% to 163.18%, indicating very good financial conditions. The value of Inventory to Net Working Capital ranges from 11.89% to 33.52%, also indicating good financial conditions. From the profitability perspective, the asset profitability ratio from 2020 to 2023 ranges from 8.57% to 7.24%, with a good financial condition. Meanwhile, the equity profitability ratio ranges from 41.36% to 30.18%, indicating a very good financial condition. Based on these results, it is recommended that the cooperative increase its liquid assets, especially cash, by increasing the number of members to boost capital investment in the cooperative.